Synthesis and Calcium Channel Antagonist Activity of New 1,4-Dihydropyridine Derivatives Containing Lipophilic 4-Imidazolyl Substituents - Navidpour, Latifeh; Miri, Ramin; Shafiee, Abbas (Arzneimittelforschung, 2004)
A group of cycloalkyl and aryl ester analogues of nifedipine (CAS 21829-25-4), in which the ortho-nitrophenyl group at position 4 is replaced by a 2-phenyl-4(5)-im-idazolyl substituent, were synthesized and evaluated as calcium channel antagonist using the high K+ contraction of guinea-pig ileal smooth muscle.The results for the symmetrical esters in cycloalkyl and aryl esters showed that increasing the length of the methylene chain in C3 and C5 ester substituents (from n = 0 to n = 3) increased activity. A comparison of the effect of cyclohexyl relative to phenyl substituent showed that cyclohexyl derivatives were more active than phenyl derivatives. In contrast to symmetrical derivatives, comparison of the activities of asymmetrical esters showed that phenyl derivatives were more active than cycloalkyl derivatives.The results demonstrate that compounds 5a, 8a, 8l and 8n had similar activity to and compounds 5b, 5c, 5d and 5i were more active than the reference drug nifedipine.The structure-activity data indicate that the 4-(2-phenyl-4(5)-imidazolyl) moiety is a bioisoester of the o-nitro group of nifedipine.
Keywords: Calcium channel antagonists; CAS 21829-25-4; 1,4-Dihydropyridines, 2-phenyl-imidazole substituents; Nifedipine, analogues